Microstructure and phase transformation of Ni-Ti-Fe-Nd quaternary shape memory alloy (Proceedings of the Mongolian Academy of Sciences, 2019)
The effect of rare earth element neodymium (Nd) addition on the microstructure and phase transformation behavior of Ni50Ti47Fe2Nd1 shape memory alloy was investigated by scanning electronic microscope, X-ray diffraction and differential scanning calorimetry. The results show that the microstructure of Ni-Ti-Fe-Nd quaternary alloy consists of NiNd3 phase, NiTi2 and the NiTi matrix. A one-step martensitic transformation is observed in the alloys. The martensitic transformation start temperature Ms 54.110C.